Nahdlatul Ulama’s Maslahah Family Movement for Sustainable Development Goals in Indonesia: Maqasid al-Sharia Perspectives - Ahmad, Maghfur; Muniroh, Siti Mumun (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
TThe present study aims to showcase the roles of the Nahdlatul Ulama’s (NU) Maslahah Family Movement (GKMNU) in achieving sustainable development goals (SDGs) from the viewpoint of maqasid al-sharia. Grounded in a qualitative research design, this study focuses on the Maslahah Family Movement in Pekalongan City and Batang Regency, Central Java, Indonesia. Data were garnered through interviews, observation, and documentation. The data were analyzed employing Miles and Huberman’s interactive analysis. Study findings demonstrate that the GKMNU was a pioneering step in building an empowered, qualified, and harmonious family with the principles of maslahah (goodness). The GKMNU in Pekalongan City concentrated more on strengthening education, training, and family counseling, whereas the GKMNU in Batang Regency emphasized aspects of economic literacy. Neither of them did not address issues on welfare, health, and economic empowerment. The problem movement’s performance needs to be optimized regarding participation, management, and program quality even though the construction of maslahah families represents a tangible expression of maqasid al-sharia and as a way of expediting development goals. The theoretical implications of this study support the notion that the maslahah family plays a crucial role in ensuring the achievement of sustainable development goals. The study also provides practical insights into policy and program development that enhances families’ endeavors to participate as agents of change in the direction of the SDGs. This study advances the synergy of integrative Islamic studies, integrating family concerns, Islamic legal principles, and political development strategies in the context of implementing the SDGs through the maqasid al-sharia-based maslahah family program.